Researching animal research - Davies, Gail; Greenhough, Beth; Hobson-West, Pru; Kirk, Robert G. W.; Palmer, Alexandra; Roe, Emma (Manchester University Press, 2024)
Animal research is part of a complex web of relations made up of humans and animals, practices inside and outside the laboratory, formal laws and professional norms, and social imaginaries of the past and future of medicine. Researching Animal Research sets out an innovative approach for understanding and intervening in the social practices that constitute animal research. It proposes the idea of the animal research nexus to draw attention to the connections that make up animal research today and to understand how these elements have become entangled over time. The authors examine moves towards openness, inclusion, and interdisciplinarity in science, and open up questions that move debates beyond polarised pro- and anti-public positions. The book is written as a collaboration and conversation between historians, geographers, sociologists, anthropologists, science and technology studies scholars, and engagement professionals, with commentaries from the arts, social sciences, and animal research sector. Through detailed qualitative analysis of regulation, care, expertise, and public engagement the book offers an unparalleled picture of the changing cultures, practices, and policies of UK animal research. By incorporating critical commentaries and examples of creative practices, it also seeks to animate and potentially transform the animal research nexus that it describes. As the social imaginaries and regulations around animal research continue to change in the UK and beyond, this book is a vital interdisciplinary contribution to the search for new ways to conduct and research animal research today.